A study in isolating circulating cancer cells from blood - Nabar, B. V. (1962)
Samples of blood from 49 cancer cases were examined for free cancer cells. Cells identified as cancer cells were found in the blood of four. Cells which looked highly suspicious of being cancer cells were isolated from the blood of nine other cases. No conclusion was possible regarding the type of cells in eight cases. This illustrates the difficulty of cytological diagnosis and shows the need for new methods of identification.